2019
DOI: 10.1002/sim.8344
|View full text |Cite
|
Sign up to set email alerts
|

Overdispersion models for correlated multinomial data: Applications to blinding assessment

Abstract: 4963 4964 LANDSMAN ET AL."marginalization," which, in turn, often entails the use of computationally intensive algorithms to integrate over the random effects. 3,4 For certain link functions and mixing distributions of random effects, as is the case with the multinomial overdispersion model (MOM) introduced in Section 2, the unconditional (on random effects) mean and variance of an outcome can be expressed analytically as functions of a global parameter and additional heterogeneity/overdispersion parameter(s).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Fourth, when we excluded outliers in effect size (two acupunctures in primary and secondary outcomes, one procedure in primary outcome, and one PT/Chiro in secondary outcome), results were attenuated, while main findings were mostly unchanged; some results in Figure S3 and Table S3. When blinding index was computed with different statistical models 49 or data structures, main findings were similar, although 2 3 3 data yielded attenuation 27,30,49 (Table S4).…”
Section: Secondary and Sensitivity Analysesmentioning
confidence: 82%
See 4 more Smart Citations
“…Fourth, when we excluded outliers in effect size (two acupunctures in primary and secondary outcomes, one procedure in primary outcome, and one PT/Chiro in secondary outcome), results were attenuated, while main findings were mostly unchanged; some results in Figure S3 and Table S3. When blinding index was computed with different statistical models 49 or data structures, main findings were similar, although 2 3 3 data yielded attenuation 27,30,49 (Table S4).…”
Section: Secondary and Sensitivity Analysesmentioning
confidence: 82%
“…Moroz et al 23 reported blinding index of 0.34/−0.2 for verum/sham and the most common blinding scenario was that participants believed they received verum regardless of the treatment received in 54 acupuncture trials, namely, wishful thinking—similar to our subgroup analysis and the finding by Braithwaite et al in comparable treatments. In contrast, Freed et al, 24 Baethge et al, 25 and Landsman et al 49 showed that overall blinding in 40 psychiatric trials is summarized as Random–Random (blinding index of 0.14/0.0 in verum/sham), and reported positive correlation between effect size and correct guesses.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations